DIAGNOSTICS OF GROUP PROSOCIAL ACTIVITIES OF ADOLESCENTS - Lavrentieva, Iryna (Theoretical and Methodical Problems of Children and Youth Education, 2023)
Belonging to a group and interpersonal communication with peers are dominant needs of adolescence. That is why group forms of organizing educational activities are relevant and effective during adolescence. The purpose of our research is to analyze and substantiate the methods of studying group activities of adolescence. The tasks of this research are: to substantiate the need for the development of the skills of group activity of adolescence; clarify the list of skills of effective group prosocial activity of adolescence; analyze and select methods of studying group activity of adolescence. In order to achieve the goal of the research and solve the tasks we used next methods: analysis of psychological and pedagogical sources on the problem, systematization, generalization, comparison and classification of the obtained data in order to substantiate the choice of diagnostic methods of research. In the process of the research, we clarified the list of skills of effective group prosocial activity of adolescence (assertiveness, optimism, self-respect, communication, cooperation, generosity) and adapted D. Franken’s questionnaire to determine the level of development of these skills. In addition, we believe that the diagnosis of the atmosphere in the group should precede any attempts to organize the team. Therefore, we chose the method of determining the cohesion index of the team by Sirosh. Since any group is a mechanism, in which all its members must work to transform it into a psychological community, into a systemic psychological organism that lives according to its own laws, each of them must perform its function. This function should be close to a person and not cause rejection. Therefore, it is important to diagnose the inclinations and abilities of team members to perform certain roles. For this purpose, we are choose the Belbin’s test, which helps to determine the role of an individual in a team. They are implementer, coordinator, creator, idea generator, researcher, expert, diplomat, performer or specialist.